2022
DOI: 10.1039/d2nr06097c
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric tungsten carbide nanoclusters as potential non-noble metal catalysts for CO oxidation

Abstract: he discovery of tungsten carbide (WC) as an analog of noble metal Pt atom is of great significance toward designing novel highly-active catalysts from the viewpoint of the superatom concept....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As mentioned in the paragraphs of the Introduction, the earlier reports that small-sized Au clusters exhibit a fantastic activity for CO oxidation reactions—revealing mechanisms of catalytic/adsorption behaviors of CO molecules on surfaces of Au clusters—were received with high-level concerns [ 7 , 11 , 32 ]. It is well-known that the presence of low-coordinated metal atoms on the surfaces of Au-based clusters play a dominant role in enhancing catalytic activity [ 33 , 34 , 35 , 36 , 37 ]. Moreover, in most cases, CO molecules prefer to be top-coordinated on the surfaces of the Au clusters, which are generally explained in terms of σ donations of electron density from CO molecules to the metals and π-back donations from metals to CO [ 34 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the paragraphs of the Introduction, the earlier reports that small-sized Au clusters exhibit a fantastic activity for CO oxidation reactions—revealing mechanisms of catalytic/adsorption behaviors of CO molecules on surfaces of Au clusters—were received with high-level concerns [ 7 , 11 , 32 ]. It is well-known that the presence of low-coordinated metal atoms on the surfaces of Au-based clusters play a dominant role in enhancing catalytic activity [ 33 , 34 , 35 , 36 , 37 ]. Moreover, in most cases, CO molecules prefer to be top-coordinated on the surfaces of the Au clusters, which are generally explained in terms of σ donations of electron density from CO molecules to the metals and π-back donations from metals to CO [ 34 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, a lot of aluminum-based superatoms, including superhalogens, , alkaline earth superatoms, superalkalis, , quasi-chalcogen superatoms, multiple valence superatoms, and noble gas superatoms have been reported. Compared with ordinary clusters, superatoms have compact structures with higher stability and symmetry and thus possess great potential to exhibit excellent performance in catalysis. Nonetheless, no studies have systematically clarified the effect of different electronic structures of superatoms on the activation and transformation of carbon–halogen bonds. Accordingly, density functional theory (DFT) calculations were carried out to study the catalytic properties of Al 12 M (M = Be, Al, C, and P) superatoms with 38, 39, 40, and 41 valence electrons, respectively, on the activation of the C–Br bond of PhBr in this work.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, superatoms can maintain their integrity just like traditional atoms when they are assembled into extended nanostructures, 27 which provides a possible way to obtain superatom-assembled catalysts to expand the practical applications of superatoms. 28,29 Recently, the CO oxidation mechanisms catalyzed by noblemetal-like superatom-assembled (WC) n (n = 1, 2, 4, and 6) 28 and (ZrO) n (n = 1-4) 29 clusters have been investigated in detail to evaluate their catalytic performance by our group. In these studies, it is found that the desorption of the CO 2 product usually becomes the rate-limiting step because these (WC) n and (ZrO) n clusters have high affinity to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, superatoms can maintain their integrity just like traditional atoms when they are assembled into extended nanostructures, 27 which provides a possible way to obtain superatom-assembled catalysts to expand the practical applications of superatoms. 28,29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation